Հայոց ցեղասպանության ճանաչման գործընթացը եվրոպական երկրներում և Հայ դատի հանձնախմբերի դերը - Լիլիթ Մատինյան (ՀՀ ԳԱԱ հրատ.)
Армянский народ, уже несколько десятилетий борется за признание и осуждение геноцида армян, а также преодоление его последствий. The Armenian people have been for several decades striving for the recognition and condemnation of the Armenian Genocide, and struggling to overcome its consequences.
Keywords: Armenian Genocide (1915)